Emplacement and flow dynamics in a small volcanic dyke swarm: The example of Mount Calanna (Etna, Italy) - Rasia Shajahan; Andrew Harris; Sara Mana; Eugenio Nicotra; Claudio Robustelli Test; Benjamin Van Wyk de Vries; Elena Zanella (Journal of Volcanology and Geothermal Research, 2024)

When the lava meets the sea: emplacement of the 2–4 ka San Bartolo lava flow field, Stromboli volcano (Italy) - Rasia Shajahan; Andrew J. L. Harris; Elena Zanella; Lucia Gurioli; Claudio Robustelli Test; Sonia Calvari; Lodovico Drovanti (Bulletin of Volcanology, 2024)
When a lava flow enters a body of water, either a lake, sea, river or ocean, explosive interaction may arise. However, when it is an 'a'ā lava flow entering water, a more complex interaction occurs, that is very poorly described and documented in literature. In this paper, we analysed the 2–4 ka San Bartolo lava flow field emplaced on the north flank of Stromboli volcano, Italy. The lava flow field extends from ~ 650 m a.s.l. where the eruptive fissure is located, with two lava channels being apparent on the steep down to the coast. Along the coast the lava flow field expands to form a lava delta ~ 1 km wide characterised by 16 lava ‘Flow’ units. We performed a field survey to characterise the features of lava entering the sea and the associated formation of different components and magnetic measurements to infer the flow fabrics and emplacement process of the lava flow system. We measured the density, porosity and connectivity of several specimens to analyse the effect of lava-water interaction on the content in vesicles and their connectivity and conducted a macroscopic componentry analysis (clast count) at selected sites to infer the character of the eroded offshore segment of the lava flow field and its component flow units. The collected data allowed us to define the main components of a lava delta fed by 'a'ā lava flows, with its channels, littoral units, ramps, lava tubes, and inflated pāhoehoe flows controlled by the arterial 'a'ā flow fronts. The spatial organisation of these components allowed us to build a three-step descriptive model for 'a'ā entering a water. The initial stage corresponds to the entry of channel-fed 'a'ā lava flow into the sea which fragments to form metric blocks of 'a'ā lava. Continued lava supply to the foreshore causes flow units to stall while spreading over this substrate. Subsequent 'a'ā lava flow units ramp up behind the stalled flow front barrier. Lava tubes extending through the stalled flow barrier feed the seaward extension of a bench made of several pāhoehoe flow units.